The Keeper : A Novel - Fisher, Suzanne Woods (Grand Rapids, Mich. : Revell, 2012)
When Julia Lapp believes her fiancé has postponed their wedding due to the advice of perpetual bachelor Roman Troyer, she sets herself on a mission to punish the nomadic beekeeper and secure the future she has dreamed of.
Keywords: Amish -- Fiction; Love stories; Christian fiction